Springing to Life: Unveiling the Transformative Effects of Trampoline Bouncing on Human Health - Dawid Bereza; Katarzyna Sokołowska; Maria Kulak; Igor Moreau; Paulina Polańska; Miriam Lang; Barbara Woch (Kazimierz Wielki University, 2024)
Introduction and Objective: In the modern era, where non-communicable diseases account for 74% of deaths, physical activity plays a crucial role in reducing mortality rates, particularly from cardiovascular causes. This article aims to assess the benefits and risks of trampoline bouncing as an exercise modality. State of Knowledge: Scientific evidence predominantly focuses on rebounding-related injuries, overshadowing the relatively underexplored benefits of trampolining. Cardiovascular advantages, including increased VO2max, are notable, with mini-trampoline exercise proving more effective than traditional running. Trampolining exhibits the potential to reduce BMI and weight, impacting cardiovascular risk factors while contributing to bone strength and mental well-being. Positive outcomes are suggested for specific groups, such as Parkinson's patients and children with disabilities. Summary: Trampoline rebounding, particularly with mini-trampolines, presents an enjoyable exercise form with significant health benefits, encompassing enhanced cardiovascular endurance, improved balance, and positive effects on bone structure and mental well-being. Despite prevalent injuries associated with trampoline use, the article highlights effective preventive measures. In conclusion, trampoline bouncing holds promise as a valuable component of a healthy lifestyle, provided adequate precautions are taken to mitigate associated risks.